2018
DOI: 10.1055/s-0038-1675383
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Early Active Mobilization on Union Rate after Ulnar Shortening Osteotomy

Abstract: Background Ulnocarpal impaction occurs when there is excessive loading between the ulnar carpus and the distal ulna. Ulnar shortening osteotomies (USOs) decompress the ulnocarpal joint. Many studies have evaluated USO but none have considered the effect of early active mobilization on union rate. Questions Does early active mobilization affect rate of union following USO? Does early active mobilization affect rate of complications following USO? Patients and Methods We performed a retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…55 Some reports also advocate early functional exercises, with incomplete short plaster fixation for 12 days and the initiation of rehabilitation exercises after plaster removal, showing no cases of nonunion. 85 However, an issue of nonunion has also been reported with too early activity. A retrospective cohort study involving 40 patients reported that immediate wrist movement after the USO resulted in a 10% rate of nonunion.…”
Section: Imaging Examinationmentioning
confidence: 99%
“…55 Some reports also advocate early functional exercises, with incomplete short plaster fixation for 12 days and the initiation of rehabilitation exercises after plaster removal, showing no cases of nonunion. 85 However, an issue of nonunion has also been reported with too early activity. A retrospective cohort study involving 40 patients reported that immediate wrist movement after the USO resulted in a 10% rate of nonunion.…”
Section: Imaging Examinationmentioning
confidence: 99%